Is there consensus in defining childhood cerebral visual impairment? A systematic review of terminology and definitions. Issue 4 (16th November 2017) - Sakki, Hanna E A; Dale, Naomi J; Sargent, Jenefer; Perez-Roche, Teresa; Bowman, Richard
Abstract : The childhood condition of visual difficulties caused by brain damage, commonly termed cortical or cerebral visual impairment (CVI), is well established but has no internationally accepted definition. Clarification of its core features is required to advance research and clinical practice. This systematic review aimed to identify the definitions of childhood CVI in the original scientific literature to describe and critically appraise a consensual definition of the condition. MEDLINE, EMBASE, PsychINFO, CINAHL and AMED databases were searched in January 2017. Studies were included if they (1) were published original research, (2) contained a childhood CVI sample, (3) contained a definition of CVI and (4) described their CVI identification/diagnostic method. Thematic analysis identified concepts within definitions and narrative synthesis was conducted. Of 1150 articles, 51 met inclusion criteria. Definitions were subdivided according to detail (descriptive definition, description not reaching definition status and diagnostic/operationalising criteria). Three themes concerning visual deficits, eye health and brain integrity were identified (each containing subthemes) and analysed individually across definitions. The most common themes were ' visual impairment' (n=20), 'retrochiasmatic pathway damage'(n=13) and 'normal/near normal eye health' (n=15). The most consensual definition identified here may not be the best quality for advancing our understanding of CVI. We argue for the alternative definition: CVI is a verifiable visual dysfunction which cannot be attributed to disorders of the anterior visual pathways or any potentially co-occurring ocular impairment. We propose reporting guidelines to permit comparison across studies and increase the evidence base for more reliable clinical assessment and diagnosis.